2020
DOI: 10.3390/ijms21217817
|View full text |Cite
|
Sign up to set email alerts
|

Truncating Variants Contribute to Hearing Loss and Severe Retinopathy in USH2A-Associated Retinitis Pigmentosa in Japanese Patients

Abstract: USH2A is a common causal gene of retinitis pigmentosa (RP), a progressive blinding disease due to retinal degeneration. Genetic alterations in USH2A can lead to two types of RP, non-syndromic and syndromic RP, which is called Usher syndrome, with impairments of vision and hearing. The complexity of the genotype–phenotype correlation in USH2A-associated RP (USH2A-RP) has been reported. Genetic and clinical characterization of USH2A-RP has not been performed in Japanese patients. In this study, genetic analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
3
14
1
Order By: Relevance
“…Third, truncating alleles are also associated with vision loss in USH2 patients, with earlier onset of and more severe retinal degeneration compared to ARRP (Inaba et al, 2020;Meng et al, 2020;Pierrache et al, 2016). However, we found that the impact of truncating alleles on retinal degeneration may be dependent on clinical diagnosis, as we found no differences in visual symptom onset or severity in those with and without truncating variants in the USH2 and ARRP subgroups.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Third, truncating alleles are also associated with vision loss in USH2 patients, with earlier onset of and more severe retinal degeneration compared to ARRP (Inaba et al, 2020;Meng et al, 2020;Pierrache et al, 2016). However, we found that the impact of truncating alleles on retinal degeneration may be dependent on clinical diagnosis, as we found no differences in visual symptom onset or severity in those with and without truncating variants in the USH2 and ARRP subgroups.…”
Section: Discussioncontrasting
confidence: 51%
“…Second, in the RUSH2A cohort, hearing loss severity in USH2 is directly related to the number of truncating alleles, as similarly noted by Hartel et al (2016) and Molina‐Ramirez et al (2020), as well as the RUSH2A study (Iannaccone et al, 2021). Third, truncating alleles are also associated with vision loss in USH2 patients, with earlier onset of and more severe retinal degeneration compared to ARRP (Inaba et al, 2020; Meng et al, 2020; Pierrache et al, 2016). However, we found that the impact of truncating alleles on retinal degeneration may be dependent on clinical diagnosis, as we found no differences in visual symptom onset or severity in those with and without truncating variants in the USH2 and ARRP subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genetic testing was performed by stepwise Sanger-sequencing using one or two panels of 15 and 27 genes in 2008–2015 [ 13 ] or next-generation sequencing using panels of 39 or 50 genes in 2015–2019 [ 17 ] or 2019 and later [ 18 ], respectively. The patients in this study underwent one of these screenings for genetic diagnosis tests.…”
Section: Methodsmentioning
confidence: 99%